Carbon Dots Fabrication: Ocular Imaging and Therapeutic Potential - Garner, Inyoung; Vichare, Riddhi; Paulson, Ryan; Appavu, Rajagopal; Panguluri, Siva K.; Tzekov, Radouil; Sahiner, Nurettin; Ayyala, Ramesh; Biswal, Manas R. (Frontiers in Bioengineering and Biotechnology, 2020)
Vision loss is a major complication in common ocular infections and diseases such as bacterial keratitis, age-related macular degeneration (AMD) and diabetic retinopathy (DR). The prevalence of such ophthalmic diseases represents an urgent need to develop safe, effective, and long-term treatments. Current therapies are riddled with drawbacks and limitations which calls for the exploration of alternative drug delivery mechanisms. Toxicity of the inorganic metals and metal oxides used for drug delivery raise safety concerns that are alleviated with the alternate use of, a natural and organic polymer which is both biocompatible and environmentally friendly. Carbon dots (CDs) represent a great potential in novel biomedical applications due to their tunable fluorescence, biocompatibility, and ability to be conjugated with diverse therapeutic materials. There is a growing interest on the exploitation of these properties for drug delivery with enhanced bio-imaging. However, there are limited reports of CD applications for ophthalmic indications. In this review, we focus on the CD potential and the development of translational therapies for ophthalmic diseases. The current review presents better understanding of fabrication of CDs and how it may be useful in delivering anti-bacterial agents, anti-VEGF molecules as well as imaging for ophthalmic applications.